Gender-specific association between blood cell parameters and hyperuricemia in high-altitude areas - Cui, Danli; Huang, Ruoying; Yongzong, Dexi; Lin, Bo; Huang, Xia; Ciren, Qimei; Zhou, Xuelian (Frontiers in Public Health, 2024)
Background: Hyperuricemia is a common metabolic disorder linked to various health conditions. Its prevalence varies among populations and genders, and high-altitude environments may contribute to its development. Understanding the connection between blood cell parameters and hyperuricemia in high-altitude areas can shed light on the underlying mechanisms. This study aimed to investigate the relationship between blood cell parameters and hyperuricemia in high-altitude areas, with a particular focus on gender differences. Methods: We consecutively enrolled all eligible Tibetan participants aged 18 to 60 who were undergoing routine medical examinations at the People's Hospital of Chaya County between January and December 2022. During this period, demographic and laboratory data were collected to investigate the risk factors associated with hyperuricemia. Results: Among the participants, 46.09% were diagnosed with hyperuricemia. In the male cohort, significant correlations were found between serum uric acid (SUA) levels and red blood cell counts (RBC), creatinine (Cr), urea, alanine transaminase (ALT), and albumin (ALB). Notably, RBC exhibited the strongest association. Conversely, in the female cohort, elevated SUA levels were associated with factors such as white blood cell count (WBC), urea, ALT, and ALB, with WBC demonstrating the most significant association. Further analysis within the female group revealed a compelling relationship between SUA levels and specific white blood cell subtypes, particularly neutrophils (Neu). Conclusions: This study revealed gender-specific associations between SUA levels and blood cell parameters in high-altitude areas. In males, RBC count may play a role in hyperuricemia, while in females, WBC count appears to be a significant factor. These findings contribute to our understanding of metabolic dynamics in high-altitude regions but require further research for comprehensive mechanistic insights.